Negative pressure of the environmental air in the cleaning area of the materials and sterilization center: a systematic review - Caroline Lopes Ciofi-Silva; Lisbeth Lima Hansen; Alda Graciele Claudio dos Santos Almeida; Julia Yaeko Kawagoe; Maria Clara Padoveze; Kazuko Uchikawa Graziano
ABSTRACT Objective: to analyze the scientific evidence on aerosols generated during cleaning activities of health products in the Central Service Department (CSD) and the impact of the negative pressure of the ambient air in the cleaning area to control the dispersion of aerosols to adjacent areas. Method: for this literature systematic review the following searches were done: search guidelines, manuals or national and international technical standards given by experts; search in the portal and databases PubMed, Scopus, CINAHL and Web of Science; and a manual search of scientific articles. Results: the five technical documents reviewed recommend that the CSD cleaning area should have a negative differential ambient air pressure, but scientific articles on the impact of this intervention were not found. The four articles included talked about aerosols formed after the use of a ultrasonic cleaner (an increased in the contamination especially during use) and pressurized water jet (formation of smaller aerosols 5μm). In a study, the aerosols formed from contaminated the hot tap water with Legionella pneumophila were evaluated. Conclusions: there is evidence of aerosol formation during cleanup activities in CSD. Studies on occupational diseases of respiratory origin of workers who work in CSD should be performed.